2010
DOI: 10.1111/j.1475-4762.2010.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

‘We are managing our own lives . . . ’: Life transitions and care in sibling-headed households affected by AIDS in Tanzania and Uganda

Abstract: This paper explores the ways that young people express their agency and negotiate complex lifecourse transitions according to gender, age and inter-and intra-generational norms in sibling-headed households affected by AIDS in East Africa. Based on findings from a qualitative and participatory pilot study in Tanzania and Uganda, I examine young people's socio-spatial and temporal experiences of heading the household and caring for their siblings following their parent's/relative's death. Key dimensions of young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 44 publications
(60 reference statements)
1
74
1
3
Order By: Relevance
“…Regarding individual social capital, the cognitive component has been found to be more important than the structural one (Story 2013). In Tanzania, studies have shown that individual social capital is important for orphans' and vulnerable children's ability to claim their land, resilience and empowerment (Evans 2011(Evans , 2012. In studies from Kagera region, the positive role of collective social capital for HIV prevention has also been established, especially through the social groups that were formed facilitating transfer of norms and knowledge important for HIV prevention (Frumence et al 2014;Frumence 2011).…”
Section: Social Capitalmentioning
confidence: 99%
“…Regarding individual social capital, the cognitive component has been found to be more important than the structural one (Story 2013). In Tanzania, studies have shown that individual social capital is important for orphans' and vulnerable children's ability to claim their land, resilience and empowerment (Evans 2011(Evans , 2012. In studies from Kagera region, the positive role of collective social capital for HIV prevention has also been established, especially through the social groups that were formed facilitating transfer of norms and knowledge important for HIV prevention (Frumence et al 2014;Frumence 2011).…”
Section: Social Capitalmentioning
confidence: 99%
“…For instance, in her research in a rural community in southern Bolivia, Punch tells us that 'schooling is available only for the first six years of primary education' (Punch 2004, p. 102) and members of a household often shared one bedroom -sleeping communally in one room with sometimes two or three children to one bed. In her research with sibling-headed households in Uganda, Evans (2010) found that, due to poverty and their caring responsibilities, many siblings were unable to continue with their primary or secondary education.…”
Section: Spacementioning
confidence: 99%
“…For instance, in her research in Bolivia, Punch (2004) has shown how older siblings may use younger siblings to help them avoid carrying out certain household chores. Evans (2010) has discussed the dynamics of sibling care within sibling-headed households affected by AIDS in Tanzania and Uganda. She found that it was through developing interdependent caring relations that these siblings were able to independently manage the household and reconfigure it as a more autonomous space.…”
Section: This Theme Of 'Interdependence' Emerges Within Both Majoritymentioning
confidence: 99%
See 1 more Smart Citation
“…Reliability in qualitative research resolves around a researcher's trustworthiness (Golafshani, 2003) and ability to provide rigour in research methods. It remained my goal to maintain a high professional standard of research and encouraged reflexivity, that is, selfawareness and self-critique (Payne & Payne, 2004) throughout all steps of the research process.…”
Section: Reliability and Reflexivitymentioning
confidence: 99%